Pengaruh Kolase Dekoratif Terhadap Kemampuan Motorik Halus Anak Usia 5-6 Tahun Di TK Nurul Usmany Muaro Paneh - Silvia Alya; Serli Marlina (Institut Nalanda, 2026)
This study aims to determine the effect of decorative collage activities on the fine motor skills of children aged 5–6 years at Nurul Usmany Kindergarten, Muaro Paneh, by considering the importance of stimulating motor development at an early age as a basis for children's academic abilities and life skills in the future. This study uses a quantitative approach with a quasi-experimental design of the One Group Pretest-Posttest type, which allows researchers to observe changes in children's abilities before and after being given treatment in the form of systematic decorative collage activities. The research subjects consisted of 15 children selected as research samples, where all participants participated in learning activities that had been structured by the researcher together with the class teacher. Data collection was carried out through direct observation and fine motor development tests, with a focus on aspects of eye-hand coordination, accuracy, and the ability to arrange and stick collage materials. The data obtained were then analyzed using the Wilcoxon test because the results of the normality test showed that the data were not normally distributed, so an appropriate non-parametric analysis method was needed. The results of the study showed an increase in the average score of children's fine motor skills from 2.87 in the pretest to 3.73 in the posttest after being given treatment in the form of decorative collage activities. This increase indicates a significant positive change in children's fine motor skills after participating in these activities repeatedly and in a directed manner. The results of the hypothesis test also showed a significance value of 0.000 which is smaller than 0.05, so it can be concluded that there is a significant influence between creative collage activities on improving fine motor skills in early childhood. These findings indicate that collage activities not only function as artistic activities, but also as an effective learning medium in developing children's fine motor skills. Thus, decorative collage activities can be used as an effective alternative learning method in early childhood education institutions to support children's physical and cognitive development optimally.